Impact of National Volume-Based Procurement on the Procurement Volumes and Spending for Antiviral Medications of Hepatitis B Virus - Yuan, Jing; Lu, Z. Kevin; Xiong, Xiaomo; Lee, Tai-Ying; Huang, Huang; Jiang, Bin (Frontiers in Pharmacology, 2022)
Introduction: Although persistent inhibition of HBV replication by antiviral therapy has shown to slow disease progression, cost-related access barriers to these essential medicines are becoming salient. The national volume-based procurement (NVBP) was piloted in China and led to substantial reduction in the list price of prescription drugs. To examine the impact of NVBP on selected antiviral medication costs per defined daily dose (DDD), procurement volumes, and spending. Methods: We employed an interrupted time series design to examine changes in cost per defined daily dose (DDD), procurement volumes, and spending for NVBP bid-winning antiviral medications (tenofovir disoproxil fumarate and entecavir) in 11 pilot cities from 2017 to 2020. Procurement transaction data were obtained from 9,454 hospitals in the Chinese Hospital Pharmaceutical Audit (CHPA) database. In the secondary analysis, the control group comprised two non-NVBP drugs (adefovir and lamivudine) procured in 11 cities not exposed to the NVBP. Results: Cost per DDD of the two hepatitis B virus (HBV) antiviral medications reduced by CNY1.598 (p=0.002) immediately following the implementation of NVBP, dropping from an average cost of CNY16.483 per DDD at baseline to CNY6.420 at the end of the observation period. NVBP implementation resulted in a substantial reduction in daily costs of antivirals and increase in monthly procurement volumes by 6.674 million DDDs (p=0.017), while monthly spending was reduced by CNY138.26 million (P=0.002). In the secondary ITS analysis with a control group, the average cost per DDD of the NVBP bid-winning antivirals declined by CNY4.537 (p<0.001), monthly procurement volumes increased by 7.209 million DDDs (P=0.002), and monthly spending dropped by CNY138.83 million (P<.001). Conclusions: Volume-based procurement piloted in China may be effective for reducing price and total expenditures and improving drug utilization, which is especially important for HBV patients who need constant access to antiviral therapies.